I sistemi museali in Toscana Primi risultati di una ricerca sul campo - Lazzeretti, Luciana (Studi e saggi, 2006)
The volume presents the results of a research promoted by an agreement between the Department of Business Sciences of the University of Florence and the Tuscany Region with the aim of defining the framework of museum systems. Since there is still no theoretical concept of a museum system, the research has framed the current situation of the region by studying "the Tuscan museum systems in place".